219k views
5 votes
How do you solve it?

How do you solve it?-example-1
User Mkul
by
5.5k points

1 Answer

5 votes

Answer:

i: x=-2, x=1

ii: x=-1/2

Explanation:

Quadratic form:

You solve i by using FOIL (First, Outside, Inside, Last) because it is a multiplication problem.


(x+2)(x-1)=0

"first" would be
x*x, which would equal
x^(2)

"outside" would be
x*-1, which would equal
-1x, or -x

"inside" would be
2*x, which would equal
2x

"last" would be
2*-1, which would equal
-2

Now you need to combine the terms so that they are one after the other


x^(2)-x
+2x-2

Combine like terms, and you should get:


x^(2) +x-2

i Solution

You need to get the variable by itself.

Subtract two from both sides


x+2=0\\x=-2

Add one to both sides.


x-1=0\\x=1

ii Solution

Add all the terms.


x+2+x-1=0\\2x+1=0\\2x=-1\\x=-(1)/(2)

User MaanooAk
by
6.0k points